Reconciling Knowledge: A Comparative Analysis of Amin Abdullah’s Integration-Interconnection Paradigm and Syed Naquib Al-Attas’s Islamization of Science - Purwaningtyas, Dhita Ayomi; Delahara, Nindhya Ayomi (Universitas Negeri Padang, 2024)
This study explores Prof. Dr. Amin Abdullah's Integration-Interconnection paradigm, which seeks to reconcile religious and secular sciences in Islamic educational contexts, particularly within Indonesian universities. While Abdullah's model emphasizes the harmonious integration of diverse scientific domains through a metaphorical